The use of palm kernel shell (PKS) as substrate material in vertical-flow engineered wetlands for septage treatment in Malaysia - Jong, Valerie Siaw Wee; Tang, Fu Ee (2015)
© IWA Publishing 2015. In this study, the treatment of septage (originating from septic tanks) was carried out in a pilot-scale, two-staged, vertical-flow engineered wetland (VFEW). Palm kernel shells (PKS) were incorporated as part of the VFEW's substrate (B-PKS), to compare its organic matter (OM) and nitrogen (N) removal efficiency against wetlands with only sand substrates (B-SD). The results revealed satisfactory OM removal with >90% reduction efficiencies at both wetlands B-PKS and B-SD. No increment of chemical oxygen demand (COD) concentration was observed in the effluent of B-PKS. Ammonia load removal efficiencies were comparable (>91% and 95% in wetland B-PKS and B-SD, respectively). However, nitrate accumulation was observed in the effluent of B-SD where PKS was absent. This was due to the limited denitrification in B-SD, as sand is free of carbon. A lower nitrate concentration was associated with higher COD concentration in the effluent at B-PKS. This study has shown that the use of PKS was effective in improving the N removal efficiency in engineered wetlands.